2009
DOI: 10.1039/b902356a
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology approaches and pathway tools for investigating cardiovascular disease

Abstract: Systems biology aims to understand the nonlinear interactions of multiple biomolecular components that characterize a living organism. One important aspect of systems biology approaches is to identify the biological pathways or networks that connect the differing elements of a system, and examine how they evolve with temporal and environmental changes. The utility of this method becomes clear when applied to multifactorial diseases with complex etiologies, such as inflammatory-related diseases, herein exemplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 97 publications
2
72
0
Order By: Relevance
“…13 Nevertheless, we stress the importance of pursuing systematic studies that clarify the latent pathways behind these phenomena. Modern systems biology offers advanced computational tools to analyze nonlinear molecular patterns, 14,15 and we believe that to assess the intriguing observation that circadian rhythms can affect the infarct size, future study design should not only include larger samples but also aim to untangle the molecular time-dynamic mechanisms underlying such a relation. …”
Section: E114 Circulation Researchmentioning
confidence: 99%
“…13 Nevertheless, we stress the importance of pursuing systematic studies that clarify the latent pathways behind these phenomena. Modern systems biology offers advanced computational tools to analyze nonlinear molecular patterns, 14,15 and we believe that to assess the intriguing observation that circadian rhythms can affect the infarct size, future study design should not only include larger samples but also aim to untangle the molecular time-dynamic mechanisms underlying such a relation. …”
Section: E114 Circulation Researchmentioning
confidence: 99%
“…115 Furthermore, 1 example of how lipids may affect pathway signaling has been nicely discussed by Wheelock et al, who revealed 77 biochemical pathways to be differentially affected between low and high fat cholesterol diet in mice, by combining liver transcriptomics and lipidomics data and mapping them onto a metabolic pathway database. 116 System biology approaches like those introduced by Wheelock et al 116 are very helpful to process high-throughput data, which is further discussed below. In addition, changes in lipid profiles, including phospholipids, ceramides, sphingomyelin, cerebrosides, cholesterol, and their oxidized derivatives, may also affect or be indicative of ischemic stroke, as indicated by Fonteh and Fisher 117 and by Fonteh et al 118 Protein microarrays are an emerging tool, competing with traditional gel-based methods (eg, 2-DE), offering a higher reproducibility and the possibility of high-throughput approaches.…”
Section: Proteomicsmentioning
confidence: 99%
“…The critical step is the construction of models from the raw dataset of transcriptomics, proteomics, and metabolomics. This may be achieved by using different mathematical techniques ranging from simple Pearson correlations to the use of ordinary differential equations (Wheelock et al, 2009). Through this modeling, fundamental concepts in the understanding of biological systems like robustness, modularity, emergence, etc.…”
Section: Comprehensive Vs Focused Metabolomicsmentioning
confidence: 99%
“…A systems biology approach does not focus on identifying a single target or mechanism of an observed phenotype. Instead it seeks to identify the biological networks or pathways that connect the differing elements of a system (Wheelock et al, 2009). When a shift in equilibrium is observed in a disease, such as altered metabolic fluxes or enzymatic activities, it can be elucidated that those components of the network that are associated with the observed shift are characteristic and potentially descriptive of the disease, and that they accordingly represent potential targets for intervention.…”
mentioning
confidence: 99%